The impact of offshoring on technical change: Evidence from Swedish manufacturing firms. Issue 3 (26th October 2021) - Baum, Christopher F.; Lööf, Hans; Stephan, Andreas; Viklund‐Ros, Ingrid
Abstract: This paper examines the link between offshoring and technical change measured by patent and total factor productivity in order to sort out the causality. It applies instrumental variable and matching approaches on a panel of more than 7000 Swedish manufacturing firms over the period 2001–2014, and identify offshoring‐related intermediate imports by the United Nations Broad Economic Categories system. Accounting for self‐selection and reverse causality, no impact of offshoring on TFP is found and only weak effect on patenting.